Implementasi Sistem Pemesanan Catering Berbasis Web Pada My Teppanyaki - Lubis, Alpin; Umam, Mizanul; Jupron (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
The rapid development of information technology encourages culinary businesses to adopt digital systems to improve service quality and operational efficiency. My Teppanyaki previously handled catering orders manually through Instagram and WhatsApp, causing difficulties in transaction management and customer data processing. This study aims to implement a web-based catering ordering system using Laravel and React technologies. The system development method used is Waterfall, consisting of requirement analysis, system design, implementation, testing, and maintenance. The application was developed using Laravel 12, React 18, Inertia.js, PostgreSQL Supabase, and Tailwind CSS. The implemented features include menu management, shopping cart, online ordering, payment confirmation, and WhatsApp integration. Black Box Testing results indicate that all system functions operate properly according to user requirements. The developed system successfully improves ordering efficiency and supports digital transformation for culinary MSMEs.